2014
DOI: 10.1021/jf501800s
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Elements, Lipoxygenase Activity, and Antioxidant Capacity of Okara as a Byproduct in Hydrothermal Processing of Soy Milk

Abstract: Minerals and antioxidative capacity of raw okara that was obtained as a byproduct from six soybean varieties during hydrothermal cooking (HTC) of soy milk were assessed. Lipoxygenase (Lox), an enzyme deteriorating the sensory characteristics of okara, was also investigated. All genotypes had very similar concentrations of Lox (4.32-5.62%). Compared to raw soybeans, the applied HTC significantly reduced Lox content in okara (0.54-0.19%) and lowered its activity to 0.004-0.007 μmol g(-1) min (-1). Correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…A significant (p<0.01) difference was observed in iron and zinc contents of soybean and okara with total iron and zinc contents in okara as 6.82 and 7.04 mg/100 g, respectively, while in soybean the respective values were 8.28 and 7.86 mg/100 g. The values in present study are within the range of those reported earlier by Varsha Rani et al (2008) for Ca, Fe and Zn of soybean. Similar results were reported by Stanojevic et al (2014) for Ca, P, Fe and Zn of okara. However, Lu et al (2013) reported higher values for Ca and Fe and lower values for K and Zn in okara.…”
Section: Total Mineral Contentssupporting
confidence: 91%
“…A significant (p<0.01) difference was observed in iron and zinc contents of soybean and okara with total iron and zinc contents in okara as 6.82 and 7.04 mg/100 g, respectively, while in soybean the respective values were 8.28 and 7.86 mg/100 g. The values in present study are within the range of those reported earlier by Varsha Rani et al (2008) for Ca, Fe and Zn of soybean. Similar results were reported by Stanojevic et al (2014) for Ca, P, Fe and Zn of okara. However, Lu et al (2013) reported higher values for Ca and Fe and lower values for K and Zn in okara.…”
Section: Total Mineral Contentssupporting
confidence: 91%
“…After extracting soymilk from soybeans, okara remained in the precipitate (Figure 4). Lox content in okara protein extracts from investigated genotypes was low ranging from 0.02 to 0.53% (Table 2), which is in agreement with literature data [34].…”
Section: Sds-page Separated Proteins From Investigated Soybean Seeds supporting
confidence: 91%
“…Therefore, the aim of this study was to assess the distribution of the two enzymes: β-amylase and lipoxygenase, during the preparation of soy protein products by hydrothermal cooking of soybeans. This research is a continuation of our previous studies on the characteristics of soy protein products obtained by the HTC process [4,7,33,34].…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…5A, 5B and 5C). When raw soybeans are ground, soybean lipoxygenases catalyse the hydroperoxidation of unsaturated fatty acids, such as linoleic and linolenic acids, and the intermediates are then lysed by soy hydroperoxide lyases to form aldehydes (Stanojevic et al, 2014). Therefore, the fresh okara contained the greatest amount of hexanal, although it decreased after autoclaving.…”
Section: Volatilesmentioning
confidence: 99%